Mutations in MINAR2 encoding membrane integral NOTCH2-associated receptor 2 cause deafness in humans and mice - Bademci, Guney (2022)
Discovery of deafness genes and elucidating their functions have substantially contributed to our understanding of hearing physiology and its pathologies. Here we report on DNA variants in MINAR2, encoding membrane integral NOTCH2-associated receptor 2, in four families underlying autosomal recessive nonsyndromic deafness. Neurologic evaluation of affected individuals at ages ranging from 4 to 80 y old does not show additional abnormalities. MINAR2 is a recently annotated gene with limited functional understanding. We detected three MINAR2 variants, c.144G > A (p.Trp48*), c.412_419delCGGTTTTG (p.Arg138Valfs*10), and c.393G > T, in 13 individuals with congenital- or prelingual-onset severe-to-profound sensorineural hearing loss (HL). The c.393G > T variant is shown to disrupt a splice donor site. We show that Minar2 is expressed in the mouse inner ear, with the protein localizing mainly in the hair cells, spiral ganglia, the spiral limbus, and the stria vascularis. Mice with loss of function of the Minar2 protein (Minar2tm1b/tm1b) present with rapidly progressive sensorineural HL associated with a reduction in outer hair cell stereocilia in the shortest row and degeneration of hair cells at a later age. We conclude that MINAR2 is essential for hearing in humans and mice and its disruption leads to sensorineural HL. Progressive HL observed in mice and in some affected individuals and as well as relative preservation of hair cells provides an opportunity to interfere with HL using genetic therapies.